PENGARUH PESTISIDA ORGANIK DAN JUMLAH BIBIT PERLUBANG PADA TANAMAN PADI (Oryza sativa L.) - Sumarmi, Sartono Joko Santoso & (FAKULTAS PERTANIAN UNIVERSITAS SLAMET RIYADI, 2008)
ABSTRACT The aim of this research was to know the influence of organic pesticide and number of seedling per hole to the disease intensity of Brown Spot (Drechslera oryzae) on Rice Plant.